STRATEGIC MANAGEMENT IN IMPROVING EDUCATION QUALITY - Altaf Syauqy Iqbal Saifani; Andriyani Andriyani; Nurmalia Lusida (Jurnal Ilmiah Edukatif, 2024)
One of the most effective methods of enhancing the quality of education is the strategic management approach.Management strategy refers to a technique of organising and managing the affairs of the organisation over a period of time. Within education, strategic management assists the organisations to understand themselves, their internal strengths and weaknesses, their external opportunities and threats as well. Such knowledge and understanding helps educational organisations develop better, effective solutions that aim at optimal learning and human resource development and management of the educational structure. The use of strategic management in educational institutions also brings about ongoing creativity, flexibility to change as well as effective usage of resources. Therefore, adoption of such approaches enables the institutions to continually improve the standard of education which in turn results in better student performance, greater stakeholder return on investment and higher competition of the institution in the market. It is therefore clear that strategic management is quite important in dealing with the problems especially in the present education landscape that is progressively becoming complicated as advanced by these institutions of learning